2017
DOI: 10.2147/dddt.s126569
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of dexamethasone and hyperbaric oxygen therapy yields better efficacy for patients with delayed encephalopathy after acute carbon monoxide poisoning

Abstract: BackgroundDelayed encephalopathy after acute carbon monoxide (CO) poisoning (DEACMP) commonly occurs after recovering from acute CO poisoning. This study was performed to assess the efficacy of the combined application of dexamethasone and hyperbaric oxygen (HBO) therapy in patients with DEACMP.Patients and methodsA total of 120 patients with DEACMP were recruited and randomly assigned into the experimental group (receiving dexamethasone 5 mg/day or 10 mg/day plus HBO therapy) and control group (HBO therapy as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 22 publications
(22 reference statements)
0
24
0
Order By: Relevance
“…Carbon monoxide (CO) poisoning is not rare and the incidence of delayed encephalopathy after carbon monoxide poisoning (DEACMP) is relatively high. Approximately 13-50% of patients with severe CO poisoning suffer from memory impairment, cognitive dysfunction, and behavioral disorders after a lucid interval (usually 2 to 60 days) of normal or apparent recovery [1][2][3], and the patients' condition was evaluated by clinical cognitive tests. This complication in clinical practice is considered DEACMP [4], which is characterized by a long course, poor prognosis, and high disability rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon monoxide (CO) poisoning is not rare and the incidence of delayed encephalopathy after carbon monoxide poisoning (DEACMP) is relatively high. Approximately 13-50% of patients with severe CO poisoning suffer from memory impairment, cognitive dysfunction, and behavioral disorders after a lucid interval (usually 2 to 60 days) of normal or apparent recovery [1][2][3], and the patients' condition was evaluated by clinical cognitive tests. This complication in clinical practice is considered DEACMP [4], which is characterized by a long course, poor prognosis, and high disability rate.…”
Section: Introductionmentioning
confidence: 99%
“…Serial DWI and 1 H-MRS measurements are useful in determining the tissue damage and long-term outcomes of delayed sequelae associated with the interval form of CO poisoning [7]. 1 H MRS is the most useful indicator in the clinical evaluation of patients with the interval KW and ML contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…HBO has been a traditional method of treating DEACMP in basic and clinical studies. Dexamethasone combined with HBO therapy has been reported to have better efficacy than HBO alone [13]. Myelin basic protein (MBP) levels in cerebrospinal fluid decreases significantly after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition,relevant clinical studies have shown that short-term NBP and HBO have a good clinical effect on the recovery of the cognitive function of DEACMP patients [27,28] .Relevant studies have also shown that DXM and HBO also have a good clinical effect on the recovery of cognitive function of DEACMP patients [29] .…”
Section: Introductionmentioning
confidence: 99%